A multi‐omic analysis of the dorsal striatum in an animal model of divergent genetic risk for alcohol use disorder. Issue 4 (16th November 2020) - Grecco, Gregory G.; Haggerty, David L.; Doud, Emma H.; Fritz, Brandon M.; Yin, Fuqin; Hoffman, Hunter; Mosley, Amber L.; Simpson, Edward; Liu, Yunlong; Baucum, Anthony J.; Atwood, Brady K.
Abstract: The development of selectively bred high and low alcohol‐preferring mice (HAP and LAP, respectively) has allowed for an assessment of the polygenetic risk for pathological alcohol consumption and phenotypes associated with alcohol use disorder (AUD). Accumulating evidence indicates that the dorsal striatum (DS) is a central node in the neurocircuitry underlying addictive processes. Therefore, knowledge of differential gene, protein, and phosphorylated protein expression in the DS of HAP and LAP mice may foster new insights into how aberrant DS functioning may contribute to AUD‐related phenotypes. To begin to elucidate these basal differences, a complementary and integrated analysis of DS tissue from alcohol‐naïve male and female HAP and LAP mice was performed using RNA sequencing, quantitative proteomics, and phosphoproteomics. These datasets were subjected to a thorough analysis of gene ontology, pathway enrichment, and hub gene assessment. Analyses identified 2, 108, 390, and 521 significant differentially expressed genes, proteins, and phosphopeptides, respectively between the two lines. Network analyses revealed an enrichment in the differential expression of genes, proteins, and phosphorylated proteins connected to cellular organization, cytoskeletal protein binding, and pathways involved in synaptic transmission and functioning. These findings suggest that the selective breeding to generate HAP and LAP mice may lead to a rearrangement of synaptic architecture which could alter DS neurotransmission and plasticity differentially between mouse lines. These rich datasets will serve as an excellent resource to inform future studies on how inherited differences in gene, protein, and phosphorylated protein expression contribute to AUD‐related phenotypes. Abstract : The dorsal striatum, a key brain region contributing to addictive behaviors, was dissected from selectively bred high and low alcohol‐preferring mice (HAP and LAP, respectively) for RNA sequencing, proteomics and phosphoproteomics analyses. 2, 108, 390 and 521 significant differentially expressed genes, proteins and phosphopeptides respectively were identified between the two lines. Network analyses revealed an enrichment in proteins involved in cytoskeletal protein binding, synaptic organization and synaptic transmission. These data sets characterizing differential gene, protein and phosphorylated protein expression in a validated model of divergent genetic risk for alcohol use disorder will serve as a valuable resource to inform future studies.